Two centuries of the equations of commutativity and associativity of exponentiation - Lóczi, Lajos (Teaching Mathematics and Computer Science, 2003)
In this survey article we guide the reader through the solution of the commutative equation of exponentiation x^y = y^x and that of the associative equation of exponentiation x^(y^z) = (x^y)^z. Various characterizations of the integer, rational, real and complex solutions are discussed together with some new results and open directions. The article is supplemented by a detailed and commented bibliography on the history of these equations.